FORMULASI DAN UJI EFEKTIVITAS MASKER PEEL OFF PATI JAGUNG (Zea mays sacchrata) SEBAGAI PERAWATAN KULIT WAJAH - Karmilah Karmilah; Nirwati Rusli (jurnal ilmiah manuntung sekolah tinggi ilmu kesehatan samarinda, 2018)
Corn is one ingredient that has been used empirically as a facial skin care. Peel-off facial mask has the advantage over the other types, it can lifted or removed as an elastic membrane easily. The purpose of this research was to formulate a peel-off facial mask of corn starch that qualifed for the evaluation of the preparation and its effectiveness test as skin care. This research is experimental research, that is making 3 formula with variation of corn starch concentration as active substance that is 5%, 10%, and 15% which aim to know optimal concentration as peel-off mask facial skin care. Based on the results of evaluation of formula A preparations with 5% active ingredient that meets the dosage evaluation, the formula that meets the evaluation of the dosage is then tested effectiveness as facial skin care. Effectiveness test using 3 respondents that is acne skin, blackhead skin, and oily skin. Test result conducted for 4 days with a view before and after use, peel-off corn starch mask capable of providing facial skin care effect is characterized by changes in skin becomes brighter, less acne and blackheads. Keywords : Peel-off facial mask, corn starch, facial skin care